Hegemonic masculinity and the stigma of failed embodiments: gender and bodily non-normativity in Sadeq Hedayat’s ‘Ābjī Khānum' and 'Dāvūd the Hunchback' - Abedinifard, Mostafa (My University, 2013)
Despite previous references to the themes of disability and bodily nonnormativity in Sadeq Hedayat’s fiction, it has yet to be extensively re-read from this viewpoint. Adopting an interdisciplinary approach, and particularly by employing thoughts and concepts from the developing areas of critical masculinity studies and disability studies, I read two understudied short stories by Hedayat: “Abji Khanom” and “Davood the Hunchback.” Both stories foreground the crucial intersection of gender and bodily nonnormativity as manifested in the social embodiments of the stories’ titular characters. While also intending the essay to serve as a very brief introduction to the above critical areas, I seek to answer the following questions about the stories: What has excluded the main characters from meaningful social interactions in their societies? What is the significance of Hedayat’s foregrounding the junction of gender and bodily nonnormativity in both stories? What might have caused each character’s highly pessimistic view toward his or her embodiment? I argue that the nonnormative bodies of both characters—whose societies legitimize a certain hierarchy of bodies—have afflicted them with stigmatized and hence socially devalued embodiments that render as liable both characters’ gender performances. This has brought about the characters’ social exclusion. Also, despite their difference in sex, both characters appear to be victims of similar hegemonic masculine ideals in their patriarchal ableist societies, which have internalized in our characters a pessimistic personal-tragedy view toward disability and bodily nonnormativity.
Keywords: gender; bodily nonnormativity